Socio-economic Effects of Introducing Halal Digital Currencies in Muslim Countries - Zyl Aliaksandr (Universitas Islam Tribakti Lirboyo Kediri, 2026)
Purpose – This study aims to analyze the socio-economic effects of implementing halal digital currencies in Muslim countries and to determine their role in shaping a fair and inclusive Islamic economy. Design/Methods/Approach – The research employs methods of theoretical analysis, comparison, and interpretation. It draws on contemporary studies that examine Islamic cryptocurrencies, central bank digital currencies (CBDCs), fintech innovations, and Shariah-compliant models. The analysis focuses on identifying both direct and indirect socio-economic effects, which are structured across macroeconomic, social, institutional, and cultural-ethical dimensions. Findings – The main findings indicate that the introduction of halal digital currencies can contribute to GDP growth, increased investment activity, and financial inclusion, as well as to the reduction of social inequality, the enhancement of trust in financial institutions, and the strengthening of institutional transparency. From the perspective of Islamic economics, halal digital currencies adhere to Shariah principles by excluding elements of riba (usury), gharar (uncertainty), and maysir (gambling), thereby promoting fair, productive, and socially oriented forms of financial interaction. Research Implications/Limitations – This paper provides a systematization of the assessed effects of halal digital currencies, taking into account economic, social, and ethical parameters, which allows for their consideration as a strategic development tool for Islamic finance. The results can be applied in the formulation of national strategies for the digital Islamic economy, the implementation of halal CBDCs, and the development of an Islamic financial inclusion framework. The research is theoretical and review-based; it does not include empirical verification of long-term effects. Future studies could involve quantitative assessments and comparative analyses of halal digital currency applications across different Islamic countries to more accurately evaluate the identified patterns. Originality/Value – The study reveals that halal digital currencies form a new paradigm for the economic and financial development of Muslim countries, in which technological innovation is integrated with spiritual principles and social responsibility.